Game Edukasi Pengenalan Peta Buta Benua Asia Berbasis Android - Yohanes Leo; Anggia Dasa Putri (UNIVERSITAS PELITA HARAPAN, 2020)
Abstract– Learning maps are very useful for studying positions, images of regions, countries and capitals. The learning media used in the teaching and learning process of blind maps only contain printed books. While the atlas and globe books belong to the class with a limited amount, and can only be lent when classes will begin. So students have difficulty if they want to repeat the learning outside the classroom. The process of learning a very large map starts from reading a printed book, then the teacher explains about the geographical location of a country, using the globe in front of the class. This makes students only able to discuss the teacher in front of the class, while the interaction happens only in one direction. The learning process method used by SDS Charitas Batam related to the big map, looks very large has shortcomings and limitations that make it difficult for students to improve the big map material. The method used in designing educational games for introducing Android-based Asian continent maps uses the GDLC method or Game Life Cyle Development and UML or Unified Modeling Language and using Construct 2 software, web 2 apk builder, Adobe Photoshop, and UML strars. The results of this study consist of an educational game for introducing Android-based Asian continents. From the results of the study, it can be concluded that the educational game of introducing a very large Asia-based Android map becomes an interesting and easy-to-understand learning media for 6th grade students of Charitas Batam SDS, increasing knowledge for students in very large Asian map problems, and learning helps learning optimally to students.Keywords: Game Education,Blind Map, GDLC, Android